Immunomodulators Containing Epicor, Colostrum, Vitamin D, Zinc, Lactobacilli and Bifidobacterium Reduce Respiratory Exacerbations in Children and Adults with Chronic Pulmonary Diseases - Snezhina Lazova; Nikolay Yanev; Nadia Kolarova-Yaneva; Tsvetelina Velikova (Sinusitis, 2022)
(1) Background: A number of studies have demonstrated the connection between developing or exacerbating chronic respiratory diseases in adults and children. However, still, few studies focus on reducing exacerbations via immunomodulation. (2) Methods: In this pilot study, a total of 25 pediatric and adult patients with bronchial asthma (BA) and chronic obstructive pulmonary disease (COPD)/persistent bacterial bronchitis (PBB) were included, administered over-the-counter (OTC) immunomodulators and followed up for 6 or 12 months. (3) Results: We observed a decrease in the frequency of exacerbations with slight improvements in functional respiratory indicators in adults on their second and third visits and a reduced number of exacerbations and improved spirometry indices in children with BA, although exacerbations requiring hospital admission remained at a similar rate. (4) Conclusions: We confirmed that the number of exacerbations of underlying chronic respiratory disease in adults and children could be reduced after the administration of OTC immunomodulators, probably by optimizing the immune resistance to common viral infections.